1999
DOI: 10.1042/bj3440895
|View full text |Cite
|
Sign up to set email alerts
|

Role of Janus kinase-2 in insulin-mediated phosphorylation and inactivation of protein phosphatase-2A and its impact on upstream insulin signalling components

Abstract: Our recent studies indicate that insulin rapidly inactivates serine/threonine protein phosphatase-2A (PP-2A) by increasing tyrosine phosphorylation on the catalytic subunit. The exact mechanism of PP-2A inactivation by insulin in vivo is unclear. The Janus kinase (JAK) family of non-receptor protein tyrosine kinases constitute a novel type of signal-transduction pathway which is activated in response to a wide variety of polypeptide ligands, including insulin. In this study we investigated the potential role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…(29) Our in vitro data (Fig. 4) support the idea that Jak2 downregulates PP2A activity via tyrosine phosphorylation of the C subunit of PP2A.…”
Section: Figsupporting
confidence: 83%
See 2 more Smart Citations
“…(29) Our in vitro data (Fig. 4) support the idea that Jak2 downregulates PP2A activity via tyrosine phosphorylation of the C subunit of PP2A.…”
Section: Figsupporting
confidence: 83%
“…Previous studies showed an IL-11-induced association of PP2A, PI3 kinase, and Yes kinase with Jak2 (28) and an increase in PP2A-Jak2 association in the insulin-stimulated rat skeletal muscle cell line L6. (29) In the latter case, insulin treatment did not increase the association between Jak2 and PP2A. In 32Dcl3 cells, the degree of association increased dramatically during agonist stimulation (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been reported that growth stimulation of cells in response to epidermal growth factor or serum [16], in response to IL-1 or TNFα [17], or in response to insulin [18] also promotes transient tyrosine phosphorylation and inactivation of PP2A. Thus, the increased phosphorylation of PP2A observed in intact cells in vitro implicates uncontrolled clinical conditions such as inflammatory or cancerous status [19].…”
Section: Introductionmentioning
confidence: 90%
“…Several studies reported that insulin 322 down-regulated PP2A Cα expression and PP2A activity in muscle 323[27][28][29], suggesting that insulin is mainly involved in the reduction of 324 PP2A Cα in C3H10T1/2 and 3T3-L1 in our experiment. These observa-325 tions led us to hypothesize that PP2A Cα regulates adipocyte differenti-326 ation by regulating the expression of adipocyte marker genes.…”
mentioning
confidence: 66%